Pemberdayaan Masyarakat Melalui Pengembangan "Kampung Markisa" Sebagai Daya Tarik Wisata di Desa Kwangsan, Sidoarjo - M Fadeli; Junjung Dias; Rindu Ainni (Journal of Indonesian Society Empowerment, 2026)
Community empowerment through the utilization of local passion fruit potential aims to improve environmental quality and economic capacity to develop it into a tourist attraction. This Thematic Student Community Service (KKN Tematik) program in Kwangsan Village was implemented to optimize passion fruit potential, from cultivation techniques to post-harvest processing. The execution method utilized a participatory approach involving students, village officials, community elements, educational institutions, and youth organizations. The implemented programs included a physical initiative to arrange the passion fruit area by installing tellis frames to improve plant growth. Meanwhile, non-physical programs comprised socialization on product diversification (such as passion fruit syrup), eco-print education for MI Darun Najah students, and socialization on social media utilization and juvenile delinquency prevention for the RW 04 Youth Organization (Karang Taruna). Social activities like morning aerobics and community mutual cooperation (gotong royong) were also conducted. The results showed an escalation in community awareness and active participation in environmental greening and village potential optimization. Socialization on cultivation, product processing, and digital marketing strategies successfully expanded residents' insights into local potential-based MSME opportunities. Furthermore, educational and social programs contributed positively to instilling creativity, ecological awareness, and digital literacy in children and youth. Overall, this program delivered a multidimensional impact in transforming Kwangsan Village into "Kampung Markisa" (Passion Fruit Village) as a sustainable tourism destination. Pemberdayaan masyarakat melalui potensi lokal tanaman markisa bertujuan meningkatkan kualitas lingkungan dan kapasitas ekonomi agar dapat dikembangkan menjadi daya tarik wisata. Kegiatan Kuliah Kerja Nyata (KKN) Tematik di Desa Kwangsan ini dilaksanakan untuk mengoptimalkan potensi markisa dari aspek budidaya hingga pascapanen. Metode pelaksanaan menggunakan pendekatan partisipatif yang melibatkan mahasiswa, perangkat desa, elemen masyarakat, lembaga pendidikan, dan organisasi pemuda. Program yang diimplementasikan meliputi program fisik berupa penataan kawasan melalui pemasangan kerangka rambatan tanaman. Sementara itu, program nonfisik mencakup sosialisasi diversifikasi produk (sirup markisa), edukasi ecoprint bagi siswa MI Darun Najah, serta sosialisasi media sosial dan pencegahan kenakalan remaja bagi Karang Taruna RW 04. Aktivitas sosial seperti senam pagi dan gotong royong juga turut dilaksanakan. Hasil KKN Tematik menunjukkan adanya eskalasi kesadaran dan partisipasi aktif masyarakat dalam pengelolaan tata hijau lingkungan. Sosialisasi budidaya, pengolahan produk, dan pemasaran digital berhasil memperluas wawasan warga mengenai peluang UMKM berbasis potensi lokal. Selain itu, program edukatif dan sosial berkontribusi positif dalam menanamkan nilai kreativitas, kepedulian ekologis, serta literasi digital pada anak dan remaja. Secara keseluruhan, program ini memberikan dampak multidimensional dalam mengonversi Desa Kwangsan menjadi "Kampung Markisa" sebagai destinasi wisata berkelanjutan.